Law No. 177 of the Year 2023 Amending Certain Provisions of the Law on the Value-added Tax Promulgated by Law No. 67 of the Year 2016 = قانون رقم 177 لسنة 2023 بتعديل بعض أحكام قانون الضريبة على القيمة المضافة الصادر بالقانون رقم 67 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic